Proceedings of the 2016 ACM Conference on Innovations in Theoretical Computer Science 2016
DOI: 10.1145/2840728.2840744
|View full text |Cite
|
Sign up to set email alerts
|

Rational Proofs with Multiple Provers

Abstract: Interactive proofs (IP) model a world where a verifier delegates computation to an untrustworthy prover, verifying the prover's claims before accepting them. IP protocols have applications in areas such as verifiable computation outsourcing, computation delegation, cloud computing, etc. In these applications, the verifier may pay the prover based on the quality of his work. Rational interactive proofs (RIP), introduced by Azar and Micali (2012), are an interactive-proof system with payments, in which the prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…In 2015, Hao and Rong [13] applied them to public goods game and repeated noise game. In 2016, Chen [14] studied rational proof problem which include multiple provers from the perspective of complexity. In model, a verifier can cross-check the answers received by asking several provers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Hao and Rong [13] applied them to public goods game and repeated noise game. In 2016, Chen [14] studied rational proof problem which include multiple provers from the perspective of complexity. In model, a verifier can cross-check the answers received by asking several provers.…”
Section: Related Workmentioning
confidence: 99%
“…However, it is a consensus that current delegate computing always introduce expensive verification costs into the system. Recently, In [14], an extension of the Zerodeterminant Strategy from two-player games to multi-player games was studied. While in [18], Rong et al investigated the influence of the strategy-selection timescale, and found that cooperation can be promoted if one permits an individual with a high payoff to hold onto his/her successful strategy for longer,which was also originally mentioned in [6].…”
Section: Related Workmentioning
confidence: 99%
“…Later, Guo et al [8] presented a one-round rational argument with polylogarithmic verification for all languages in P. Campanelli and Gennaro [4] studied the composability of rational proofs and presented a sequentially composable rational proof for arithmetic circuits. Chen, McCauley, and Singh [5] studied rational proofs that allows multiple provers, and showed that multiple rational provers are strictly more powerful than one.…”
Section: Related Workmentioning
confidence: 99%
“…In 2014, Guo et al [20] studied rational arguments with limited computing capacity of provers. In 2016, Chen et al [21] studied the rational proof of multiple provers from complexity theory. In 2017, Inasawa and Yasunaga [22] proposed a three-message delegation scheme in which the verifier was rational.…”
Section: Introductionmentioning
confidence: 99%